Performance-based metamodel for healthcare facilities. - Cimellaro, Gian Paolo (Earthquake engineering & structural dynamics.)
This paper introduces an organizational model describing the response of the Hospital Emergency Department (ED). The metamodel is able to estimate the hospital capacity and the dynamic response in real time and to incorporate the influence of the damage of structural and non-structural components on the organizational ones. The waiting time is the main parameter of response and it is used to evaluate the disaster resilience index of healthcare facilities. Its behaviour is described using a double exponential function and its parameters are calibrated based on simulated data. The metamodel covers a large range of hospital configurations and takes into account hospital resources, in terms of staff and infrastructures, operational efficiency and existence of an emergency plan, maximum capacity and behaviour both in saturated and over-capacitated conditions. The sensitivity of the model to different arrival rates, hospital configurations and capacities and the technical and organizational policies applied during and before the strike of the disaster has been investigated. This model becomes an important tool in the decision process either for the engineering profession or for the policy makers.